ANALISIS PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada Business Unit SPBU PT. Putra Kelana Makmur Group Batam) - zunaidah .; Ardi Novarandi arif budiman (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
The purpose of this research is to analyse and find out the influence of motivation and organization culture to employee’s performance of Business Unit SPBU PT. Putra Kelana Makmur Group Batam.   There are two variables in this research. The Independent variables are motivation and organization culture, and dependent variable is employee’s performance. Population in this research are all the employee’s of Business Unit SPBU PT. Putra Kelana Makmur Group Batam, 198 peoples. Sample taken with cluster divided from work contract status, the sample is 132 respondents. Data analyse is used double linear regression analysis for testing the influence of motivation and organization culture towards the employee’s performance of Business Unit SPBU PT. Putra Kelana Makmur Group Batam.The result of this research, a) motivation is positively and significantly influenced the employee’s performance. b) Organization culture also influenced positively and significantly to employee’s performance. c) Motivation and organization culture simultaneously, positively and significantly influenced the employee’s performance. Increasing employee’s motivation can give them more challenge and achievement. Giving support to the employee for participating in worker’s society. Increasing organization culture through giving more attention from leader, implement open communication system and treats to all the employees with fairness.